Penguatan Fungsi Pengawasan DPRD terhadap Tenaga Kerja Asing di Daerah Investasi - Suhendra Sultan Al Alif; Abdul Rasyid Saliman (Universitas Semarang, 2025)
This research aims to analyze the supervision of the presence of foreign workers by Commission II of the Bangka Tengah Regional People's Representative Council (DPRD) and to formulate strategies for strengthening supervision in order to protect the rights of local workers. The background of this research is based on the increasing flow of foreign investment in Central Bangka, which encourages the entry of foreign workers into strategic sectors, particularly mining and processing. This condition has given rise to various challenges, ranging from overlapping authorities, weak verification of foreign workers' competencies, to the suboptimal implementation of knowledge transfer programs. The urgency of the research lies in the importance of the supervisory function of the DPRD as a legislative pillar in the trias politica system to ensure labor accountability and social justice. This research uses a socio-legal approach with qualitative methods through interviews, field observations, and document studies. The research results indicate that the supervision of foreign workers has not been optimal due to the absence of an integrated information system, weak inter-agency coordination, and irregularities in the validity periods of foreign workers permits. The novelty of this research lies in the empirical analysis of the role of the DPRD within the context of local institutions. This research concludes that an integrated technology-based monitoring system, competency verification SOPs, and the formation of cross-agency teams are needed as strategic recommendations to strengthen the supervisory function of the DPRD. Penelitian ini bertujuan untuk menganalisis pengawasan terhadap keberadaan tenaga kerja asing (TKA) oleh Komisi II DPRD Bangka Tengah serta merumuskan strategi penguatan pengawasan dalam rangka melindungi hak tenaga kerja lokal. Latar belakang penelitian ini didasarkan pada meningkatnya arus investasi asing di Bangka Tengah yang mendorong masuknya TKA ke sektor-sektor strategis, khususnya pertambangan dan pengolahan. Kondisi ini memunculkan berbagai tantangan, mulai dari tumpang tindih kewenangan, lemahnya verifikasi kompetensi TKA, hingga belum optimalnya program transfer pengetahuan. Urgensi penelitian terletak pada pentingnya fungsi pengawasan DPRD sebagai pilar legislatif dalam sistem trias politica untuk memastikan akuntabilitas ketenagakerjaan dan keadilan sosial. Penelitian ini menggunakan pendekatan socio-legal dengan metode kualitatif melalui wawancara, observasi lapangan, dan studi dokumen. Hasil penelitian menunjukkan bahwa pengawasan TKA belum berjalan optimal karena tidak adanya sistem informasi terpadu, lemahnya koordinasi antar lembaga, dan ketidakteraturan masa berlaku izin TKA. Kebaruan penelitian ini terletak pada analisis empirik peran DPRD dalam konteks kelembagaan lokal. Penelitian ini menyimpulkan bahwa dibutuhkan sistem pengawasan terpadu berbasis teknologi, SOP verifikasi kompetensi, serta pembentukan tim lintas lembaga sebagai rekomendasi strategis untuk memperkuat fungsi pengawasan DPRD.